ANALISIS PENINGKATAN KETERAMPILAN POLA DASAR YANG DIBUTUHKAN DALAM OLAHRAGA BASKET DI SEKOLAH DASAR - Indriani Prastika, Inggit; Edwita; Rahmi Darman, Dina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the low mastery of basic basketball skills, especially shooting, among elementary school students caused by limited coordination, inappropriate equipment, and conventional learning methods. The purpose of this research is to analyze effective strategies for improving basic basketball movement skills in elementary schools. This study used a research and development approach and a systematic review of 13 relevant scientific articles. The findings show that audiovisual media, video tutorials, and innovative learning models such as manipulative movement, Direct Instruction, Project Based Learning, and Group Investigation are effective in improving students’ interest, understanding of basic techniques, learning completeness, and motor skills. In addition, coordination exercises and modified equipment support better skill development in accordance with elementary students’ motor characteristics. The study concludes that improving basic basketball skills in elementary school requires an integrated and holistic approach combining learning media, instructional models, and physical task modification.